Antonio Gramsci’s reading of Machiavelli: between the history of philosophy and political theory - Sánchez Berrocal, Alejandro (Anales del Seminario de Historia de la Filosofía, 2023)
This article begins by reconstructing Antonio Gramsci’s textual reception of and interest in Machiavelli. Then, the two parts of the paper seek to offer an exposition of the way, originality and consequences according to which Gramsci interprets Machiavelli. On the one hand, in his historical specificity, and, on the other hand, as a political theorist offering tactical and strategic applications. Through various themes, such as the formation of the nation-state, Machiavelli’s precocious Jacobinism, the relationship between ruling class and masses or considerations on the economic constitution of the USSR, we show the ways in which Machiavelli appears in Gramsci’s work, what the Florentine’s presence means at different moments of it and how it dialogues with the rest of the Gramscian conceptual universe.
Keywords: Gramsci; hegemony; Machiavelli; national-popular; nation-state; people